Leslie Hewitt - Rabinowitz, Cay Sophie 1965-; Lee, Lisa 1978-; Respini, Eva 1976- (Osmos Books, 2018)
Featured in the Guggenheim's 2015 landmark 'Photo-Poetics' exhibition, New York-based artist Leslie Hewitt (born 1977) is one of the most revered artists working between photography and sculpture. Collaboration has been a central part of Hewitt's art, including projects with William Cordova and Matt Keegan, and her ongoing work with cinematographer Bradford Young exploring the Menil Collection archive of civil rights-era photographs. That cinematic rumination on historicity and the relationship of the archive to memory, minimalism, lived experience and time, sets an exemplary precedent for this first monograph surveying Hewitt's oeuvre. Edited by Cay Sophie Rabinowitz with texts by Nana Adusei-Poka and others, and designed by Garrick Gott, with color reproductions and in-depth critical essays, this book offers rare insights into the artist's extensive personal archive of images, concepts and ideas
Preface / Cay Sophie Rabinowtiz -- With confidence and persistence / Nana Adusei-Poku -- Exhibition history: 2004-2008 -- Studio -- Exhibitions history: 2008-2011 -- Collaborations -- Exhibition history: 2011-2014 -- Opacities and matrices / Lisa Lee -- Dialogues -- Leslie Hewitt and Eva Respini in conversation -- Exhibition history: 2015-2018
Keywords: Hewitt, Leslie -- 1977-; Hewitt, Leslie / 1977- / Catalogs; Hewitt, Leslie / 1977- / Interviews; Hewitt, Leslie / 1977-; Art, Modern / 21st century / Catalogs; Photography, Artistic / 21st century / Catalogs; Installations (Art) / 21st century; Installations (Art); Photography, Artistic; 2000-2099; Catalogs; Interviews; Bildband